PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PENDAMPINGAN OLIMPIADE SAINS NASIONAL BIDANG EKONOMI DI SMAK KESUMA MATARAM - Kurnia Martikasari; Natalina Premastuti Brataningrum; Nicolas Bayu Kristiawan (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The National Science Olympiad in Economics is one of the competitions held every year for senior high school students, especially at SMAK Kesuma Mataram. Students need to well prepare to take part in this olympics. In the national science olympiad, students learn to be able to analyze and solve problems. Therefore, mentoring activity for the national science olympiad in Economics are needed. This activity aims to student to have new experiences on how to study well and finally be able to analyze and solve the National Science Olympiad in Economics. This mentoring activity applies a problem-based learning model. The results of this mentoring activity show that students can have new experiences about how to learn well. This is indicated by students having motivation to first read the material that has been delivered even though there is material that has not been understood. Second, there is a change in students' perceptions of accounting for better. At first, most of students had the perception that accounting material was difficult, especially they had never received accounting material. However, after the implementation of mentoring, most students found it easier to understand Accounting material. In addition, after participating in this mentoring activity, students can analyze and solve National Science Olympiad in Economics cases in Economics. One of the indicators is 3 (60%) students out of 5 students who participated in this mentoring activity passed National Science Olympiad in regency level. The number of students from SMAK Kesuma Mataram who passed National Science Olympiad in regency level also increased from the previous year, from 2 students to 3 students. Keywords: Problem Based Learning, National Science Olympiad, Economic, Accounting.